Implementasi Bimbingan Kelompok Berbasis Al-Qur’an untuk Meningkatkan Kesabaran Mahasiswa - Jannati, Zhila (diterbitkan oleh Program Studi Bimbingan dan Konseling FKIP Universitas Sriwijaya Jl. Palembang Prabumulih KM 3.2 Palembang-Indonesia Email: jkk@fkip.unsri.ac.id, 2023)
Not everything in this world will be according to human wishes. Sometimes sadness and happiness come and go. Only a human being who has patience can endure in the way of Allah swt. With patience, humans will get a very big reward on the side of AllahSWT. This research has a goal, namely to find out how the implementation of al-qur'anbased group guidance is to increase student patience. A qualitative approach with descriptive research methods was used by researchers in this study. Ten students of theIslamic Counseling Guidance Study Program were selected to be research subjects using a purposive sampling technique with a population of 30 people. Data were analyzed using data analysis techniques, namely qualitative descriptive techniques after collecting data using interview techniques, documentation and observation. The results of this study were (1) the implementation of al-Qur'an-based group guidance to increase student patience was carried out using five stages, namely the formation, transition, activity, conclusion, and closing stages, and (2) an increase occurred in student patience in where students have been able to hold themselves from despair, calm, do not complain easily, and assume that everything will return to Allah SWT.